Ocorrência e suscetibilidade a drogas antifúngicas de Candida não-albicans, no Hospital Universitário Cassiano Antônio de Moraes, Vitória-ES - Klein, Nazareth Magnago (2006)
This study was carried out to evaluate the prevalence and distribution of the species of Candida spp. Isolated from several biological materials obtained from patients interned at the Hospital Universitário Cassiano Antonio de Moraes (HUCAM), Vitória-ES, during the period of January 2003 to December 2005, and to describe the profile of susceptibility of Candida non-albicans to antifungal drugs. The identification of the species of Candida albicans was made into the chromogenic medium CHROMagar-Candida® and confirmed through the positive induction of a germinative tube and/or clamidoconídeo. The identification of the species nonalbicans was made through of morphologic and biochemical patterns and through the commercial system API 20 C AUX. The profile of susceptibility to the antifungal drugs amphotencin B itraconazole and fluconazole was established by the reference method, broth microdilution, according to the document M27-A2 from CLSI, 2002. A comparative study was conducted, using the method Etest® for the strains of Candida tropicalis being included at this stage, the drug voriconazole. The results showed that 268 isolates of Candida spp. were obtained during the period of the study and, in general, a predominance was observed in the isolation of Candida nonalbicans (54%) at HUCAM, including C. tropicalis (26%), C. parapsilosis (14%), C. glabrata (10%), C. krusei (2%), C. guilliermondii (1.5%) and C. Lusitaniae (0.5%). There was a relevant transition in the prevalence of Candida non-albicans during the three years of study, oscillating in the frequency from 39% of the isolations in 2003 to 74% in 2005. The non-albicans species were more isolated from urine (47%), followed by blood (39%) and catheter (8%). The biggest occurrences were noticed in patients interned at the General Intensive Care Unit and Medical Clinic with a rate of 23% in each one. The resistance rate noticed for the non-albicans species to fluconazol was of 4% and, of susceptible dose-dependent (SDD) to fluconazole and to itraconazole was of 2% and 3% respectively (methodology CSLI). With the use of this methodology, it was observed that 98% of the strains of C.tropicalis were sensitive to fluconazole and to itraconazole, but 2% were SDD to these drugs. When the method Etest® was used, 2% of these samples were resistant to both drugs and 19% were SDD to itraconazole. No isolated of Candida non-albicans was resistant to amphotericin B or to voriconazole. All the isolates of Candida albicans were sensitive to the three drugs analyzed. With this study it was concluded that there was a striking tendency to the isolation of C. non-albicans, with the predominance of C. tropicalis. Reduced susceptibility to fluconazole and itraconazole was also noticed only in the species C. tropicalis, C. krusei and C. glabrata, reinforcing the concern about a high number of isolations of these species non-albicans at HUCAM. The Etest® method using the medium of agar Casitone, showed an excellent concordance with the reference method to the drugs amphotericin B (100%) and fluconazole (96%). However, for the itraconazole this agreement was of 62%.